A lethal voting: preferential vote and political parties in Peru - Tuesta Soldevilla, Fernando (2013)
The paper analyzes the impact that preferential voting has had on elections and the party system, particularly in the case of Peru. It presents, in the first place, the issue of preferential voting as an element of the electoral system. Then, it continues with the study of the particular case of Peru, in which it indicates its origin, the mechanics it follows, the impact on the Parliament and its evaluation.